Perbedaan Nilai Rerata Kvp % Prediksi Dan Kv % Prediksi Antara Orang Dengan Indeks Massa Tubuh Normal Dan Di Atas Normal Di Universitas Muhammadiyah Surakarta - Primasakti, Irkhamyudhi; , dr. Riana Sari, Sp.P; , dr. Sri Wahyu Basuki, M.Kes (2015)
Introduction: FVC dan VC is a parameter on spirometri checkup that to know the abnormality of pulmonary restriction. Some Researchs had reported that BMI abnormal have the abnormality in their pulmonary restriction. Purpose: This research is to know the difference of the mean value FVC% prediction and VC% prediction between BMI normal people and abnormal in Muhammadiyah Surakarta University. Methode: The Research design that used is observational analitic methode with cross sectional approachment. The size of sample 35 people per group. Sample which used are mens with ages between 18-25 years who fulfill the restriction criteria. The take of sample use the purposive sampling tehcnique. The differences of the mean FVC% prediction and VC% prediction is analyzed use hypothesis testing which is the t test two unpaired and Mann-Whitney with SPSS 20.0 program for windows. Research result: There is the difference significantly of the mean value FVC% prediction and VC% prediction in people with normal body weight index (FVC 83,9580 % dan VC 112,8063 %) and the BMI abnormal (FVC 70,4734% dan VC 79,7374%) by the. The hypothesis test result of t test two unpaired got 0,000 (p<0,05) dan Mann-Whitney got significancy0,001 (p<0,05). Conclusion: The mean value of FVC% prediction and VC% prediction between the BMI normal and abnormal in Muhammadiyah Surakarta University got the difference significantly by the statistic.